Reduce stress and the risk of burnout by using yoga techniques. Pilot study - Zok, Agnieszka; Matecka, Monika; Bienkowski, Artur; Ciesla, Magdalena (Frontiers in Public Health, 2024)
Introduction This article examines the effectiveness of yoga in managing stress, with a particular focus on work-related stress. Yoga combines physical postures, breath control, and meditation, and has gained recognition for its potential to relieve stress. Purpose This study aimed to investigate the motivating factors behind individuals adopting yoga exercises and to assess the effects of regular yoga practice, with a particular focus on age-related differences. Additionally, we aimed to compare participants’ expectations with the actual results of their yoga practice. Methods To achieve this, we conducted a comprehensive survey using an online form, which was completed by 520 yoga practitioners. Participants were surveyed about their motivation, the effects they experienced, and the type of yoga they practiced. Results The results showed that the most common motivation for individuals practicing yoga was stress reduction. Additionally, the analysis of the effects of regular yoga practice demonstrated a significant reduction in stress levels, with experienced practitioners reporting lower stress levels compared to beginners. In conclusion, the study suggests that regular yoga practice can be an effective way to reduce stress levels. Conclusion Dynamic forms of yoga, which incorporate fluid movements and synchronized breathing techniques, are highly effective approaches to stress management and relief. These findings highlight the value of yoga as a tool for individuals of all ages seeking stress relief and overall well-being. Another advantage of yoga practice is its affordability and lack of negative side effects.